SKP2- and OTUD1-regulated non-proteolytic ubiquitination of YAP promotes YAP nuclear localization and activity - Fan Yao (Nature Portfolio, 2018)
Regulation of Yes-associated protein (YAP) through the Hippo pathway is well established, but its Hippo-independent regulation remains to be elucidated. Here, the authors show that non-proteolytic ubiquitination presents another means of YAP regulation, promoting its nuclear localization and activity.